Analysing the different Entrepreneurship Education initiatives for the development of a conducive and motivating entrepreneurial ecosystem in Mauritius - Roopchund, Randhir (Management and Entrepreneurship: Trends of Development, 2020)
Mauritius ambitions to be a high-income economy and therefore seeks to develop an entrepreneurial culture by furthering entrepreneurship knowledge in its education system. The government is keen in encouraging youths to develop an entrepreneurial mindset through significant reforms in both secondary and tertiary education. The setting of the African Leadership University in Mauritius tries to fill the knowledge gap in leadership skills necessary for the development of entrepreneurship education. The African Leadership University is also using different pedagogies of education to create the right skills set for students so that they can embrace leadership and entrepreneurial roles in future. The current research uses a qualitative approach using multi-case methods and content analysis to analyse the initiatives for empowering potential youth entrepreneurs in secondary and tertiary education in the Mauritian context. The purpose of the research is therefore to analyse the different entrepreneurship education initiatives being undertaken to promote the right entrepreneurial culture both at secondary and tertiary level of education. The government has made Business and Entrepreneurship Education compulsory from Grade 7 till Grade 9 in secondary schools. The research findings show that students in secondary school are motivated to develop entrepreneurial knowledge and the subject highly meaningful. Conversely, there is lack of entrepreneurship courses at tertiary level especially in public universities. The African Leadership University is using the flipped classroom teaching pedagogy for promoting entrepreneurship with their students. Besides, NGOs such as YUVA are also supporting youths and entrepreneurs to upgrade their business knowledge. It is worth noting that SMEs already represented 40% of the GDP of our economy in the year 2017.JEL Classification: A20, M13